First Report of Canker Disease Caused by Botryosphaeria parva on Cork Oak Trees in Italy - Linaldeddu, B. T.; Franceschini, A.; Luque, J.; Phillips, A. J. L. (Plant Disease, 2007)
A survey was carried out in the spring of 2003 to study the fungi associated with declining trees in a cork oak (Quercus suber L.) forest located in Sassari Province, Sardinia, Italy (40°52?N, 9°01?E) at an altitude of 150 m (above sea level). Several isolates obtained from live twigs and branches showing sunken necrotic bark lesions were identified as Fusicoccum parvum Pennycook EF1-α: 100%). Representative sequences of both regions were deposited at GenBank (ITS: Accession No. DQ487157; EF1-α: Accession No. DQ487158). Pathogenicity tests were carried out on seven 2-year-old cork oak seedlings maintained in a greenhouse at 14 to 26°C with the B. parva strain CBS 119937 obtained in this study. A mycelial plug (3 to 4 mm2) taken from the margin of an actively growing colony on PDA was put in a shallow wound made by a scalpel on the basal part of the stem of each seedling. Sterile PDA plugs were placed into similar wounds on three control seedlings. The inoculation points were wrapped in Parafilm to retain moisture for 1 week. After 4 weeks, all seedlings inoculated with B. parva died and showed a collapse of the stem cortical tissues associated with dark brown discolorations and vascular necrosis measuring 10.9 ± 0.4 cm. No symptoms were visible in the control seedlings. The pathogen was reisolated from all the inoculated seedlings, thus fulfilling Koch's postulates. The results confirm the virulence of this fungus and point to its possible involvement in the aetiology of cork oak decline. B. parva is a cosmopolitan, plurivorous pathogen causing disease in several hosts of economic importance, such as grapevine (3), kiwi (2), and Eucalyptus spp. trees (1). To our knowledge, this is the first report of B. parva causing canker disease on cork oak trees. References: (1) A. Gezahgne et al. S. Afr. J. Bot. 70:241, 2004. (2) S. R. Pennycook and G. J. Samuels. Mycotaxon 24:445, 1985. (3) A. J. L. Phillips. Phytopathol. Mediterr. 41:3, 2002. (4) B. Slippers et al. Mycologia 96:83, 2004.
doi: 10.1094/PDIS-91-3-0324Adoi: 10.1094/PDIS-91-3-0324AThe following values have no corresponding Zotero field: publisher: Scientific Societies
Keywords: canker disease; Cork oak; Italy (voyant)